2016
DOI: 10.1371/journal.pone.0164251
|View full text |Cite
|
Sign up to set email alerts
|

Readability and Content Assessment of Informed Consent Forms for Phase II-IV Clinical Trials in China

Abstract: PurposeTo explore the readability and content integrity of informed consent forms (ICFs) used in China and to compare the quality of Chinese local ICFs with that of international ICFs.MethodsThe length, readability and content of 155 consent documents from phase II-IV drug clinical trials from the Third Xiangya Hospital Ethics Committee from November 2009 to January 2015 were evaluated. Reading difficulty was tested using a readability formula adapted for the Chinese language. An ICF checklist containing 27 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…An informed consent form (ICF) is mandatory and essential in most studies involving human subjects as it is a primary vehicle for disclosure of information and documentation of consent [ 1 , 2 ]. An observation of the current research practice reveals that ICFs continue to increase in length and complexity in an attempt to comply with regulatory requirements [ 3 6 ], which increasingly require more and more elements to address past and present unethical practice [ 7 , 8 ]. Lengthy and complex ICFs decrease the ability of potential participants to comprehend the ICF content and exercise their autonomy in decision making to participate in a study [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An informed consent form (ICF) is mandatory and essential in most studies involving human subjects as it is a primary vehicle for disclosure of information and documentation of consent [ 1 , 2 ]. An observation of the current research practice reveals that ICFs continue to increase in length and complexity in an attempt to comply with regulatory requirements [ 3 6 ], which increasingly require more and more elements to address past and present unethical practice [ 7 , 8 ]. Lengthy and complex ICFs decrease the ability of potential participants to comprehend the ICF content and exercise their autonomy in decision making to participate in a study [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, clearly explaining all relevant information for IC has proven to be a major challenge [ 7 ]. Challenges include the complexity and amount of information [ 8 ] and the readability and understandability of IC documents [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by G. Wen on Chinese and international ICFs revealed a difference between national and international forms in terms of readability and content integrity, with a benefit towards the latter. The Chinese forms were evaluated as difficult to read, with poor descriptions of alternatives, a low degree of information on future data/sample processing, inclusion criteria or unpredictable risks [15] Interestingly, the growing number of pages does not result in the patient's better understanding. Out of 90 patients taking part in the perception questionnaire conducted by A. S. Meza-Lopez et al, 84 stated that they understood the ICFs; however, a closer analysis revealed that 2% -57% misunderstood the basic concepts of the research, including the name of the study drug, randomization and placebo [11].…”
Section: Quality Of Informed Consent As a Challenge Of The 21st Centrymentioning
confidence: 99%